Live attenuated pseudorabies virus expressing envelope glycoprotein E1 of hog cholera virus protects swine against both pseudorabies and hog cholera. - van Zijl, M (1991)
To investigate whether live attenuated pseudorabies virus (PRV) can be used as a vaccine vector, PRV recombinants that expressed envelope glycoprotein E1 of hog cholera virus (HCV) were generated. Pigs inoculated with these recombinants developed high levels of neutralizing antibodies against PRV and HCV and were protected against both pseudorabies and hog cholera (classical swine fever).